(untitled) (INNOTEC, 2013)
Uruguay is a dairy country where predominates regulations in bovine milk. Goat milk is a complete food, suitable for children and seniors, but there are few studies in our country. We studied the hygienic-sanitary quality and composition of milk in Saanen goats during a complete lactation. 25 animals were used. Samples were obtained from the milk tank every two weeks. Total aerobic mesophilic count (TAMC), coliforms and Staphylococcus coagulase positive, Dörnic acidity, pH, composition, fatty acids and Somatic Cell Count (SCC) were analized. The results were: TAMC: 3,85±0,69 ufc/ml Log10, SCC 6,91±.0,55 cel/ml Log10, CT 2,47±0,84 ufc/ml Log10, SCP 1,13±0,29 ufc/ml Log10. Values of fat 3,58±0,69%, protein 2,71±0,07% 2,71% and lactose 3,84±0,10%, acidity 14,19±0,39 ºD, pH 6,66±0,06 and density 1,026±0,26 g/ml were obtained, being consistent with work per-formed in healthy animals and reported for the same breed. Caproic, caprylic and capric acids account for a 12% of the total fatty acids, higher than the cow milk (≈5%).The values obtained are a useful basis for future goat milk regulation. Considering its difference with cow’s milk specifi c stand-ards are necessary.